The Persebaran Produksi Tanaman Biofarmaka Menurut Kecamatan di Kota Bogor Tahun 2020-2022 - Navila, Ilma (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2024)
Indonesia has a variety of plants that are often used by the community as traditional medicine. Therefore, it is necessary to conduct research on the distribution of medicinal plants based on geographic information systems that aim to determine the distribution of medicinal plants (biopharmaceuticals), in addition to providing information and adding insight to the public about the distribution of medicinal plants in sub-districts in the city of Bogor. The method used in this study involved collecting spatial data.